A 16-year-old boy with emphysematous gastritis and oesophageal candidiasis. (11th September 2014) - Yusef, Daniel; Waran, Ariane; Vamvakiti, Ekaterini
Abstract : Emphysematous gastritis is a rare and frequently fatal condition caused by invasion of gas-forming bacteria into the gastric wall. There have only been a handful of reported cases in the paediatric population, and none of these have evidence of candidal infection or mucormycosis. Patients typically present with abdominal pain, vomiting, malaena and haematemesis. Risk factors for emphysematous gastritis are those that interfere with the natural barriers to infection in the stomach. Diagnosis is made on the basis of typical appearances on abdominal CT. Treatment is generally conservative with surgery reserved for failed medical management or later complications. Antimicrobial cover should be broad with a low threshold for antifungals. It is important to look for predisposing factors for this condition, perhaps including an assessment of the patient's immunocompetency. We present a 16-year-old boy with global developmental delay who presented with this condition associated with candidal infection.